ADHD Symptoms and Sex Moderate the Relation Between Protective Behavioral Strategies and Alcohol Use Among Treatment-Mandated College Students. Issue 1 (2nd January 2021) - Looby, Alison; Cleveland, Carolyn S.; Zimmerman, Lauren; Hartung, Cynthia M.
Abstract: College students with attention deficit/hyperactivity disorder are likely to engage in alcohol use and experience alcohol-related problems. Use of protective behavioral strategies is related to fewer alcohol-related consequences. However, this association has not been sufficiently examined in relation to attention deficit/hyperactivity disorder symptoms, which could alter the likelihood of utilizing protective behavioral strategies. This study examined whether attention deficit/hyperactivity disorder symptoms moderate the relationship between protective behavioral strategies and alcohol use, and whether this differs by sex. Participants were 125 treatment-mandated college students (58.6% male; M age = 19.50 years) who completed measures of attention deficit/hyperactivity disorder symptoms, protective behavioral strategies, and past-2-week drinking. There was a significant 3-way interaction such that drinking was highest when protective behavioral strategy use was low and hyperactivity/impulsivity symptoms were high, but only for women. There was also a significant protective behavioral strategy by inattention interaction, as students with high inattention and low protective behavioral strategy use consumed the most drinks. Interventions to enhance use of protective behavioral strategies may effectively decrease alcohol use for college students with attention deficit/hyperactivity disorder symptoms, particularly women.